Nuclear Import Analysis of Two Different Fluorescent Marker Proteins into Hepatocyte Cell Lines (HuH-7 Cell) - Haryanto, Aris; Kann, Michael (Universitas Gadjah Mada, 2005)
The application of fluorescent proteins as expression markers and protein fusion partners has provedimmensely valuable for resolving the organization of biological events in living cells. EGFP and DsRed2 arecommonly fluorescent marker protein which is used for biotechnology and cell biology research. The presentstudy was designed to identify the expression vector that suitable to ligate with DNA encoding HBV coreprotein for intracellular localization study in hepatocyte cell, which were expressed as fusion proteins. We alsocompared and quantified the expressed fluorescent protein which predominantly localized in the cellcompartment. The results indicated that DsRed2 shown as less than ideal for intracellular localization study ofthan EGFP, because of its tetrameric structure of the fluorescent protein and when fused to a protein of interest,the fusion protein often forms aggregates in the living cells. In contrast, EGFP fluorescent protein shown a muchhigher proportion of cytoplasmic localization, thus being more suitable for analysis of intracellular localizationthan DsRed2 fluorescent protein. EGFP fluorescent protein is also capable to produce a strong green fluorescencewhen excited by blue light, without any exogenously added substrate or cofactor, events inside living cell canthus be visualized in a non-invasive way. Based on our present quantitative data and some reasons above shownthat EGFP is more suitable than DsRed2 as a fluorescent marker protein for intracellular localization study intoHuH-7 cell.Keywords: EGFP, DsRed2 fluorescent protein , HuH-7 cell, HBV, intracellular localization